Radio frequency identification mechanization - Osama saadwai (International Scientific and Current Research Conferences, 2020)
A library is a developing creature. As it fills in size the issues related with the support and security of the records likewise develops. The scientists have consistently helped the curator in taking care of their issues. To tackle the issues of orchestrating records all together they have given order plot. To take care of the issues of looking through reports they have given recording rules. To robotize the counter exercises they gave us standardized tags. Standardized tags have served the bookkeepers and libraries for quite a while, and now it is gradually getting supplanted by radio frequency identification.